Screening for transfusion transmissible infections using rapid diagnostic tests in Africa: a potential hazard to blood safety?. Issue 2 (8th December 2015) - Prugger, C.; Laperche, S.; Murphy, E. L.; Bloch, E. M.; Kaidarova, Z.; Tafflet, M.; Lefrère, J.‐J.; Jouven, X.
Abstract : Rapid diagnostic tests (RDTs) are routinely used in African blood centres. We analysed data from two cross‐sectional studies representing 95 blood centres in 29 African countries. Standardized panels of sera containing varying concentrations of anti‐human immunodeficiency virus (HIV) antibodies (Ab), hepatitis B virus antigen (HBsAg) and antihepatitis C virus (HCV) Ab were screened using routine operational testing procedures at the centres. Sensitivity of detection using RDTs was high for HIV Ab‐positive samples, but low for intermediately HBsAg (51·5%) and HCV Ab (40·6%)‐positive samples. These findings suggest that current RDT use in Africa could pose a hazard to blood safety.